The Impact of Mental Health on the Job Performance of Medical and Non-Medical Workers - Abdullah, Rabiya; Suryoputro, Antono; Adi, Mateus Sakundarno (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
In terms of their impact on the workforce, mental disorders in the workplace are a major concern. Poor mental health and stress can have a negative impact on worker performance and productivity, job attachment, collegial communication, physical performance, and daily functioning. The objective of this study is to investigate the relationship between mental health and job performance in medical and non-medical workers at general region hospital X. A quantitative cross-sectional study was conducted on 222 respondents, two of whom were medical and two of whom were non-medical workers, using a DASS-21 questionnaire and a job performance questionnaire. The findings show a relationship between age and job performance among medical and non-medical employees at General Region Hospital X. There is no significant relationship between mental health and job performance among medical workers. Gender, age, employment status, and work period all had a significant relationship with non-medical workers' job performance. Anxiety, gender, and age all have a significant relationship in non-medical workers. The conclusions is 44.1% reported poor job performance, 14.5% reported depression, 30.7% reported anxiety, and 11.3% reported stress. In both medical and non-medical workers, there was a significant interaction between anxiety and gender on job performance. Anxiety, gender, and age all had an impact on non-medical workers' job performance. It is critical to develop new health policies to prevent and treat mental health issues while also improving job performance. intervene and assist workers suffering from mental illnesses. Training and management on mental health, a conducive workplace, and social support can enhance productivity and decrease mental problems.